Perancangan Data Warehouse Sistem Informasi Eksekutif untuk Data Akademik Program Studi - Eko Prasetyo; Lukito Edi Nugroho; Marcus Nurtiantara Aji (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
This research examines the design of data warehouse that are the result of data integration and abstraction from various academic applications that accommodate the needs of history and archiving data to support executive information systems in the academic field. Identification of the executive reports use reference of the program accreditation forms, internal academic quality audit questionnaires, Dean’s annual reports, self-evaluation forms of Competitive Grant Program, features of the existing EIS, and features of executive data on the university academic administration website. The subject of this research is student data based on chronological stages starting from candidates selection process, new students, and students during lectures. The success of data warehouse design is determined by the right description of the business events, data completeness and validity, data mart design using metrics bus architecture, star schema design and ETL process to integrate, extract, cleanse, transform and load it into the data warehouse.